Modifiers of non-specific symptoms in occupational and environmental syndromes. - Spurgeon, A (1996)
Many occupational and environmental health hazards present as an increased reporting of non-specific symptoms such as headache, backache, eye and respiratory irritation, tiredness, memory problems, and poor concentration. The pattern and number of such symptoms is surprisingly constant from hazard to hazard suggesting that common psychological and social factors, not directly related to the exposure may be involved. A recent workshop (see acknowledgements) was held to review the pattern of symptoms in varying hazardous situations and the psychological mechanisms behind the genesis and maintenance of symptoms. The involvement of both direct physicochemical and psychological mechanisms in symptom generation and reporting in any situation was discussed and is reported here. A model that identifies the issues that need to be considered in any epidemiological study based on the incidence or prevalence of non-specific symptoms is proposed.